Epidemiological study of elderly people affected by drug intoxication in the state of Paraíba: a portrait of a decade (Research, Society and Development, 2021)
This study aimed to investigate the epidemiological profile of elderly people affected by drug intoxication in Paraíba, between the years 2007 to 2017. It was an epidemiological, observational, retrospective, analytical and documentary study, of the quantitative type, in which data were collected from queries to the database of the Information System for Notifiable Diseases (SINAN), made available by the Informatics Department of the Unified Health System (DATASUS). Variables such as year, city of notification, sex, age, education, circumstances of the type of poisoning and evolution of cases were analyzed. For the analysis of the associations between the variables, the Chi-Square Test of Independence was applied, in which p